Community participation in the planning of local destination management : Participacija zajednice u planiranju lokalnog destinacijskog menadžmenta - Koščak, Marko (Array, 2020)
In this paper we suggest that modern tourism planning of a destination should include participation from all levels of the community (direct stakeholders, local residents and differing age groups) if the participatory process is to be extensive and universal within the community. We see participatory planning as a critical success factor in seeking to satisfy the requirements of the modern paradigm of sustainability and responsibility in tourism. A community-based approach to tourism development is a prerequisite to sustainability. This focuses on community involvement in the planning and development process, and developing the types of tourism, which generate real social and economic benefits to local communities. Representing the interests and fulfilling the needs of various users is one reason for enabling their participation. Interestingly, children & youth are often overlooked in this regard even though adults may not adequately represent their needs. An important outcome of participatory planning is the process of collective learning that takes place through the underlying process of dialogue. We will refer in the paper to parallel research conducted with colleagues in Slovenia focusing in detail on the role of children & youth in the participatory process of developing sustainable tourism at a local level. This includes a view that planning for sustainable tourism development is an effort to shape the future. Among stakeholders and community participants, children & youth have a significant voice in the future and to a strong degree should have the right to engage in development. The paper seeks to assess the role of participatory structures in planning and development and in the role of children & youth as stakeholders in the planning of local destination management.